2020
DOI: 10.1038/s41598-020-72608-0
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic characteristics and improved magnetic performance of Ca–La–Co-substituted strontium hexaferrite nanomagnets

Abstract: Recent studies on next-generation permanent magnets have focused on filling in the gap between rare-earth magnets and rare-earth-free magnets, taking into account both the cost-effectiveness and magnetic performance of the magnetic materials. As an improved rare-earth-free magnet candidate, here, Ca-substituted M-type Sr-lean hexaferrite particles within a nano- to micro-scale regime, produced using an ultrasonic spray pyrolysis method, are investigated. Theoretically, the maximum coercivity (Hc) can be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…9. Determination of M s can be based on the law of approach to saturation (LAS), in which H -dependent M obeys the following expression: 50 where a ′ and χH associated with the inhomogeneities and spontaneous magnetization of domains, respectively, are ignorable as considering a homogeneous ferromagnet at low temperatures and high fields. In other words, eqn (1) can be rewritten as:where b is a parameter associated with the magneto-crystalline anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…9. Determination of M s can be based on the law of approach to saturation (LAS), in which H -dependent M obeys the following expression: 50 where a ′ and χH associated with the inhomogeneities and spontaneous magnetization of domains, respectively, are ignorable as considering a homogeneous ferromagnet at low temperatures and high fields. In other words, eqn (1) can be rewritten as:where b is a parameter associated with the magneto-crystalline anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…[ 215 ] Efforts have been made to enhance the magnetic characteristics of hexaferrite by cationic substitution to meet a variety of applications. [ 148,216 ] These includes efforts on altering the intrinsic properties of hexaferrites by replacing with either single or multiple trivalent metal ions such as La 3+ , [ 217–221 ] Tb 3+ , [ 222,223 ] Nd 3+ , [ 138–140,224–226 ] Eu 3+ , [ 227 ] Dy 3+ , [ 228,229 ] Sm 3+ , [ 230,231 ] Cr 3+ , [ 232,233 ] Al 3+ , [ 185,186,234,235 ] Gd 3+ , [ 236–238 ] Sc 3+ , [ 239 ] Er 3+ , [ 240–242 ] Pr 3+ , [ 243 ] Yb 3+ , [ 244 ] Ce 3+ , [ 245 ] La 3+ –Pr 3+ , [ 246 ] La 3+ –Nd 3+ , [ 247 ] Nd 3+ –Sm 3+ , [ 248 ] Nb 3+ –Y 3+ , [ 249 ] La 3+ –Ce 3+ , [ 250 ] Er 3+ –Cr 3+ , [ 251 ] Dy 3+ –Nd 3+ –Pr 3+[ 252 ] or a suitable mix of divalent and trivalent ions such as Tb 3+ –Mn 2+ , [ 253 ] Nd 3+ –Co 2+ , [ 254 ] Gd 3+ –Co 2+ , [ 255 ] Pr 3+ –Mn 2+ , [ 256 ] Sm 3+ –Co 2+ , [ 257 ] La 3+ –Co 2+ , [ 258 ] La 3+ –Mn 2+ , [ 259 ] Pr 3+ –Co 2+ , [ 260 ] Cu 2+ –Cr 3+ , [ 261 ] Al 3+ –Mg 2+ , [ 262 ] Ce 3+ –Zn 2+ , [ 263 ] Ce 3+ –Co 2+ , [ 264 ] Gd 3+ –Mn 2+ ‐Co 2+ , [ 265 ] Ca 2+ –La 3+ –Co 2+[ 266 ] or tetravalent Zr 4+[ 267 ] or a divalent and tetravalent ions such as Co 2+ –Si 4+ , [ 268 ] Cu 2+ –Zr 4+,[ 269 ] Zr 4+ –Co 2+ , [...…”
Section: Properties Of Hexagonal Ferritesmentioning
confidence: 99%
“…It has even been reported that in some cases, there is a preferential stacking (arrangement) in hexagonal-shaped particles. Therefore, the crystals tend to grow perpendicular to the c-axis, which makes the easy stacking of the platelet-like particles [44]. This effect is most likely due to the magnetic interactions between platelets [45].…”
Section: Morphological Characteristicsmentioning
confidence: 99%